STUDI KEANEKARAGAMAN MAMALIA PADA BEBERAPA TIPE HABITAT DI STASIUN PENELITIAN PONDOK AMBUNG TAMAN NASIONAL TANJUNG PUTING KALIMANTAN TENGAH - Yanto Santosa; Eko Prastio Ramadhan; Dede Aulia Rahman (Media Konservasi, 2008)
Indonesia harbours the highest mammal diversity in the world with 436 species, of which 51 % are endemic. Kalimantan itself comprises of 222 species of mammals of which 44 species are endemic. This research was conducted to determine mammal diversity and mammal’s variety differences in every habitat type found in Pondok Ambung Tropical Rainforest Research Station. The methods used were strip transect, concentration count and trapping. The research indicated as many as 22 species of mammals belonging to 12 families and 6 orders were found in 5 habitat types within Pondok Ambung Tropical Rainforest Research Stations. Peat forest showed the greatest variety of mammals with 17 species followed by lowland forest with 13 species, shrub land with 4 species, post-burned forest with 4 species and heath forest with 2 species.Keywords : Mammal diversity, habitat, Pondok Ambung